Forest management certification growth in Malaysia: the case of the Malaysian Timber Certification Scheme - Mohamad Kasim, Mohamad Roslan; Mohamed, Johar; Harun, Zubaidah; Manikam, Murughan; Gandaseca, Seca; Zaki, Pakhriazad Hassan (Malaysian Forester, 2024)
The Malaysian Timber Certification Scheme’s (MTCS) forest management certifications, which consist of natural forest certification and plantation forest certification, were introduced in 2001 and 2014, respectively. Since it has been two decades since MTCS’s forest management certifications were adopted and practised, a study was conducted to analyse the growth of MTCS’s natural forest certification between 2002 and 2021, MTCS’s plantation forest certification between 2014 and 2021, and the contributing factors. The data obtained from the Malaysian Timber Certification Council’s annual reports between 2002 and 2021 were analysed using descriptive analysis. The Compound Annual Growth Rate (CAGR) and Average Annual Growth Rate (AAGR) of the MTCS-certified natural forest area were 4% and 1.3% respectively. For the MTCS-certified plantation forest area, the CAGR and AAGR were 36% and 39%, respectively. Several factors have contributed to the growth of forest management certifications in Malaysia, such as the Malaysian Timber Certification Council’s (MTCC) phased or step-wise approach, the Sarawak state government’s forest policy reform, the endorsement of MTCS by the Programme for the Endorsement of Forest Certification (PEFC), and the implementation of global timber legality legislations, among others. While it is evident that there is significant growth in the MTCS-certified forest areas and certificate holders between 2002 and 2021, it is important to maintain and expand this certification.